A positive electrode material with double ion doping and wood ear derived carbon composite modification, and preparation method and application thereof

A dual-ion doped and wood ear-derived carbon composite modified positive electrode material addresses the limitations of Na3V2(PO4)2F3 by expanding lattice spacing and enhancing electron transmission, resulting in improved specific capacity and structural stability in sodium ion batteries.

CN118978139BActive Publication Date: 2024-12-31SHIJIAZHUANG TIEDAO UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411433377.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2024-12-31
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

The electrochemical performance of Na3V2(PO4)2F3 positive electrode materials in sodium ion batteries is limited by low conductivity and significant capacity decay during cycling.

Method used

A dual-ion doped and wood ear-derived carbon composite modified positive electrode material is prepared by adding NaF, KF, NH4H2PO4, NH4VO3, C4H6MnO4·4H2O, and wood ear particles, followed by heating, freeze-drying, and calcination to form Na3-x KxV2-yMny(PO4)2F3@BF, enhancing lattice spacing and electron transmission.

Benefits of technology

The composite material improves specific capacity, reaction kinetics, and structural stability, reducing electrode impedance and side reactions, with a capacity retention rate of 102.86% after 200 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118978139B_ABST
    Figure CN118978139B_ABST
Patent Text Reader

Abstract

The present invention provides a positive electrode material with dual ion doping and wood ear derived carbon composite modification, and a preparation method and application thereof. The preparation method comprises the following steps: (1) adding NaF, KF, NH4H2PO4, NH4VO3, C4H6MnO4·4H2O and wood ear particles to water in sequence under stirring, and dispersing them evenly to obtain a mixed solution; (2) heating and stirring the mixed solution to obtain a gel state mixture; (3) freeze drying to obtain a freeze-dried gel; (4) grinding and then performing a first calcination; (5) grinding the first calcination product and then performing a second calcination. The positive electrode material with dual ion doping and wood ear derived carbon composite modification of the present invention is Na 3‑x K x V 2‑y Mn y (PO4)2F3@BF can effectively improve the structural stability and cycle stability of the positive electrode material, and the capacity retention rate can reach up to 102.86% after 200 cycles at a 0.2 C rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a double-ion doped and wood ear-derived carbon composite-modified positive electrode material, and a preparation method and application thereof. Background Art

[0002] Sodium ion batteries have become a hot topic among researchers due to their high safety factor, abundant sodium resources and low price. In sodium ion batteries, electrode materials are an important component. + It provides the battery with a higher redox potential, which is directly related to the battery's operating voltage and reversible capacity.

[0003] Among various cathode materials, Na3V2(PO4)2F3 (abbreviated as NVPF), as a representative member of sodium superionic conductor (NASICON) structure compounds, is considered to be a promising cathode material due to its superior structural stability, fast ion transport, high working potential, etc. However, Na3V2(PO4)2F3 cathode materials have relatively low conductivity and large capacity decay in the late cycle.

[0004] Therefore, it is necessary to provide an improved technical solution to address the above-mentioned deficiencies in the prior art. Summary of the invention

[0005] The object of the present invention is to provide a double ion doped and wood ear derived carbon composite modified positive electrode material, so as to help solve or improve the problem that the electrochemical performance of Na3V2(PO4)2F3 positive electrode material needs to be further improved.

[0006] In order to achieve the above-mentioned object, the present invention provides the following technical scheme: a preparation method of a dual-ion doped and wood ear-derived carbon composite modified positive electrode material, comprising the following steps: (1) adding NaF, KF, NH4H2PO4, NH4VO3, C4H6MnO4·4H2O and wood ear particles to water in sequence under stirring, and dispersing them uniformly to obtain a mixed solution; (2) heating and stirring the mixed solution to obtain a gel-state mixture; (3) cooling and freeze-drying to obtain a freeze-dried gel; (4) grinding the freeze-dried gel, and performing a first calcination after grinding to obtain a first calcination product; (5) grinding the first calcination product, and performing a second calcination after grinding to obtain the dual-ion doped and wood ear-derived carbon composite modified positive electrode material; the dual-ion doped and wood ear-derived carbon composite modified positive electrode material is Na 3-x K x V 2-y Mn y (PO4)2F3@BF.

[0007] Preferably, in step (4), the first calcination temperature is 250-350°C, and the calcination time is 3.5-4.5 h; in step (5), the second calcination is carried out in an argon environment, the second calcination temperature is 710-790°C, and the calcination time is 5.0-6.5 h.

[0008] Preferably, in step (2), the heating temperature is 60-100°C; in step (3), the freeze-drying temperature is -70~-50°C.

[0009] Preferably, Na 3-x K x V 2-y Mn y In (PO4)2F3@BF, x=0.01-0.04, y=0.05-0.1.

[0010] Preferably, the particle size of the fungus particles is 1-2 mm; 3-x K x V 2-y Mn y In (PO4)2F3@BF, the mass percentage of wood ear-derived carbon is 1%-5%.

[0011] The present invention also proposes a positive electrode material doped with double ions and composite modified with wood ear derived carbon, which adopts the following technical scheme: a positive electrode material doped with double ions and composite modified with wood ear derived carbon, wherein the positive electrode material doped with double ions and composite modified with wood ear derived carbon is prepared by the method described above.

[0012] The present invention also proposes a positive electrode, which adopts the following technical solution: a positive electrode, wherein the positive electrode adopts the positive electrode material compositely modified by double ion doping and wood ear derived carbon as described above.

[0013] The present invention also proposes a sodium ion battery, which adopts the following technical solution: a sodium ion battery, wherein the sodium ion battery adopts the positive electrode as described above.

[0014] Beneficial effects:

[0015] In the preparation method of the positive electrode material of the present invention, by using K + and Mn 2+ Doping Na3V2(PO4)2F3, the two ions can produce a synergistic effect, expand the lattice spacing of Na3V2(PO4)2F3, and broaden the Na + The ion diffusion path accelerates the Na +The composite modification of wood ear-derived carbon (porous carbon derived from wood ear) allows the material particles to grow inside and outside the pores of the derived carbon, which significantly improves the performance of the material. This can be mainly attributed to: first, when wood ear-derived carbon is added, the surface area of ​​the material increases, which increases the electrochemical active reaction sites of the material, thereby increasing the specific capacity of the composite material; second, the three-dimensional porous structure formed after the calcination of wood ear is conducive to the Na + It plays a good role in promoting the extraction / embedding and transmission of electrons, which can reduce the electrode impedance, improve the reaction kinetics of the material, and thus improve the cycle stability and rate performance of the material; thirdly, the full compounding of the wood ear-derived carbon to the material can effectively avoid the direct contact between the electrode material and the electrolyte, reduce the corrosion of the electrolyte on the electrode material, effectively reduce the occurrence of side reactions, and play a relatively important protective role for the material. Fourthly, the porous carbon derived from wood ear has an excellent stable structure, which can effectively avoid the agglomeration of active materials and relieve the stress generated by the active materials in the electrochemical process, thereby enhancing its structural stability.

[0016] The dual-ion doped and wood ear-derived carbon composite modified positive electrode material of the present invention can effectively improve the structural stability and cycle stability of the positive electrode material, and its first-week discharge specific capacity and cycle capacity retention rate are significantly better than those of Na3V2(PO4)2F3 positive electrode material.

[0017] The capacity retention rate of the double-ion doped and wood ear-derived carbon composite modified positive electrode material of the present invention after 200 cycles at a 0.2 C rate can reach up to 102.86%. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them:

[0019] Figure 1 XRD diagram; wherein, (a) is the XRD diagram of NKVMPF@1%BF, NKVMPF@2%BF, NKVMPF@3%BF, NKVMPF@4%BF, NKVMPF@5%BF and NKVMPF positive electrode materials, and (b) is a local enlarged diagram of (a);

[0020] Figure 2are SEM images; wherein, (a) is the SEM image of NKVMPF, (b) is the SEM image of NKVMPF@1%BF, (c) is the SEM image of NKVMPF@2%BF, (d) is the SEM image of NKVMPF@3%BF, (e) is the SEM image of NKVMPF@4%BF, and (f) is the SEM image of NKVMPF@5%BF;

[0021] Figure 3 Transmission electron microscope observation images; (a) is the TEM image of NKVMPF@3%BF; (b) is the HRTEM image of NKVMPF@3%BF;

[0022] Figure 4 Thermogravimetric curves of NKVMPF@3%BF and NKVMPF;

[0023] Figure 5 This is the full XPS spectrum of NKVMPF@3%BF;

[0024] Figure 6 K is NKVMPF@3%BF 2p , Mn 2p , C 1s and V 2p XPS spectrum of K 2p XPS spectrum of Mn 2p XPS spectrum of C 1s XPS spectrum of V 2p XPS spectrum of

[0025] Figure 7 O of NKVMPF@3%BF 1s , P 2p 、F 1s and Na 1s XPS spectrum of O 1s XPS spectrum of (b) P 2p XPS spectrum of F 1s XPS spectrum of Na 1s XPS spectrum of

[0026] Figure 8 The results of the specific surface area test are shown in Figure 1. (a) is the N2 adsorption / desorption isotherm of NKVMPF, and (b) is the N2 adsorption / desorption isotherm of NKVMPF@3%BF.

[0027] Fig. 9The graphs are the charge and discharge test results of NKVMPF@1%BF, NKVMPF@2%BF, NKVMPF@3%BF, NKVMPF@4%BF, NKVMPF@5%BF and NKVMPF positive electrode materials; wherein (a) is the cycle performance graph, and (b) is the rate performance graph;

[0028] Fig.10 CV curves; (a) is the CV curve of NKVMPF, (b) is the CV curve of NKVMPF@1%BF, (c) is the CV curve of NKVMPF@2%BF, (d) is the CV curve of NKVMPF@3%BF, (e) is the CV curve of NKVMPF@4%BF, and (f) is the CV curve of NKVMPF@5%BF;

[0029] Fig.11 The electrochemical impedance spectroscopy and first-week charge-discharge test results of NKVMPF@1%BF, NKVMPF@2%BF, NKVMPF@3%BF, NKVMPF@4%BF, NKVMPF@5%BF and NKVMPF positive electrode materials are shown in Figure 1; (a) is the electrochemical impedance spectroscopy of NKVMPF@1%BF, NKVMPF@2%BF, NKVMPF@3%BF, NKVMPF@4%BF, NKVMPF@5%BF and NKVMPF positive electrode materials, and (b) is the first-week charge-discharge curve of NKVMPF@1%BF, NKVMPF@2%BF, NKVMPF@3%BF, NKVMPF@4%BF, NKVMPF@5%BF and NKVMPF positive electrode materials;

[0030] Fig.12 is the impedance real part (Z') of NKVMPF@1%BF, NKVMPF@2%BF, NKVMPF@3%BF, NKVMPF@4%BF, NKVMPF@5%BF and NKVMPF electrodes in the low frequency region and ω -1 / 2 The relationship curve diagram of

[0031] Fig.13 These are the weekly charge and discharge curves of NKVMPF@1%BF, NKVMPF@2%BF, NKVMPF@3%BF, NKVMPF@4%BF, NKVMPF@5%BF and NKVMPF; among them, (a) is the weekly charge and discharge curve of NKVMPF, (b) is the weekly charge and discharge curve of NKVMPF@1%BF, (c) is the weekly charge and discharge curve of NKVMPF@2%BF, (d) is the weekly charge and discharge curve of NKVMPF@3%BF, (e) is the weekly charge and discharge curve of NKVMPF@4%BF, and (f) is the weekly charge and discharge curve of NKVMPF@5%BF. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.

[0033] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0034] Aiming at the problem that the electrochemical performance of the current Na3V2(PO4)2F3 positive electrode material needs to be further improved, the present invention provides a method for preparing a positive electrode material by double ion doping and wood ear derived carbon composite modification.

[0035] The preparation method of the dual-ion doped and wood ear derived carbon composite modified positive electrode material of the embodiment of the present invention comprises the following steps: (1) adding NaF, KF, NH4H2PO4, NH4VO3, C4H6MnO4.4H2O and wood ear particles to water in sequence under stirring, and dispersing them evenly to obtain a mixed solution; (2) heating and stirring the mixed solution to obtain a gel state mixture; (3) cooling and freeze drying to obtain a freeze-dried gel; (4) grinding the freeze-dried gel, and performing a first calcination after grinding to obtain a first calcination product; (5) grinding the first calcination product, and performing a second calcination after grinding to obtain a dual-ion doped and wood ear derived carbon composite modified positive electrode material; the dual-ion doped and wood ear derived carbon composite modified positive electrode material is Na 3-x K x V 2- y Mn y (PO4)2F3@BF.

[0036] In the preparation method of the positive electrode material of the present invention, by using K + and Mn 2+ Doping Na3V2(PO4)2F3, the two ions can produce a synergistic effect, expand the lattice spacing of Na3V2(PO4)2F3, and broaden the Na + The ion diffusion path accelerates the Na +The composite modification of wood ear derived carbon makes: first, when wood ear derived carbon is added, the surface area of ​​the material increases, the electrochemical active reaction sites of the material are increased, and the specific capacity of the composite material is increased; second, the three-dimensional porous structure formed after calcination of wood ear is more conductive to Na + It plays a good role in promoting the extraction / embedding and transmission of electrons, which can reduce the electrode impedance, improve the reaction kinetics of the material, and thus improve the cycle stability and rate performance of the material; thirdly, the full compounding of the wood ear-derived carbon to the material can effectively avoid the direct contact between the electrode material and the electrolyte, reduce the corrosion of the electrolyte on the electrode material, effectively reduce the occurrence of side reactions, and play a relatively important protective role for the material. Fourthly, the porous carbon derived from wood ear has an excellent stable structure, which can effectively avoid the agglomeration of active materials and relieve the stress generated by the active materials in the electrochemical process, thereby enhancing its structural stability.

[0037] In a preferred embodiment of the method for preparing the dual-ion doped and wood ear-derived carbon composite modified positive electrode material of the present invention, in step (4), the temperature of the first calcination is 250-350°C (for example, 250°C, 275°C, 300°C, 325°C or 350°C), and the calcination time is 3.5-4.5 h (for example, 3.5 h, 4 h or 4.5 h); in step (5), the second calcination is carried out in an argon environment, the temperature of the second calcination is 710-790°C (for example, 710°C, 730°C, 750°C, 770°C or 790°C), and the calcination time is 5.0-6.5 h (for example, 5.0 h, 5.5 h, 6 h or 6.5 h).

[0038] In a preferred embodiment of the method for preparing the dual-ion doped and wood ear-derived carbon composite modified positive electrode material of the present invention, in step (2), the heating temperature is 60-100°C (for example, 60°C, 70°C, 80°C, 90°C or 100°C); in step (3), the freeze-drying temperature is -70~-50°C (for example, -50°C, -55°C, -60°C, -65°C or -70°C).

[0039] In a preferred embodiment of the method for preparing a positive electrode material of the present invention which is double-ion doped and compositely modified with wood ear derived carbon, Na 3-x K x V 2-y Mn yIn (PO4)2F3@BF, x = 0.01-0.04 (e.g., 0.01, 0.02, 0.03 or 0.04), y = 0.05-0.1 (e.g., 0.05, 0.06, 0.07, 0.08, 0.09 or 0.1). + and Mn 2+ Excessive doping may destroy the stability of the crystal structure and hinder the Na + Therefore, the appropriate ion doping amount is a necessary condition for optimizing the electrochemical performance of Na3V2(PO4)2F3 cathode materials.

[0040] In a preferred embodiment of the method for preparing the positive electrode material of the present invention with dual ion doping and wood ear derived carbon composite modification, the particle size of the wood ear particles is 1-2 mm; Na 3-x K x V 2-y Mn y In (PO4)2F3@BF, the mass percentage of wood ear derived carbon is 1%-5% (for example, 1%, 2%, 3%, 4% or 5%). When the amount of wood ear derived carbon is too small, the protective and conductive effects of the wood ear derived carbon are limited and insufficient to maintain the stability of the material structure; when the amount of wood ear derived carbon is too much, the mass proportion of the wood ear derived carbon in the positive electrode material increases, which reduces the specific capacity of the material. Therefore, adding an appropriate amount of wood ear derived carbon can improve the charge and discharge specific capacity, rate performance and cycle performance of the material.

[0041] The present invention also proposes a dual-ion doped and wood ear-derived carbon composite modified positive electrode material. The dual-ion doped and wood ear-derived carbon composite modified positive electrode material of the embodiment of the present invention is prepared by the method described above.

[0042] The present invention also provides a positive electrode. The positive electrode of the embodiment of the present invention adopts the positive electrode material compositely modified by double ion doping and wood ear derived carbon as mentioned above.

[0043] The present invention also provides a sodium ion battery. The sodium ion battery in the embodiment of the present invention adopts the positive electrode as described above.

[0044] The double-ion doped and wood ear-derived carbon composite modified positive electrode material of the present invention and its preparation method and application are described in detail below through specific examples.

[0045] The reagents used in the embodiments of the present invention can be purchased commercially; for example, the main sources of reagents used in the following embodiments: sodium fluoride (analytical grade, 98%), citric acid monohydrate (analytical grade, 99.5%) and manganese acetate tetrahydrate (analytical grade, 99%) were purchased from Aladdin Reagent; sodium metavanadate (analytical grade, 99%) and ammonium dihydrogen phosphate (analytical grade, 99%) were purchased from Sinopharm Chemical Reagent Co., Ltd.; potassium fluoride (analytical grade, 99%) was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0046] Example 1

[0047] The preparation method of the dual-ion doped and wood ear derived carbon composite modified positive electrode material of this embodiment comprises the following steps:

[0048] (1) NaF, KF, NH4H2PO4, NH4VO3, C4H6MnO4·4H2O, C6H8O7·H2O and black fungus particles (wherein the amount of NaF is 0.01 mol, the sum of the amounts of NaF and KF, the sum of the amounts of NH4VO3 and C4H6MnO4·4H2O, and the stoichiometric ratio of NH4H2PO4 to C6H8O7·H2O is 3:2:2:3; the stoichiometric ratio of NaF to KF is 2.975:0.025, and the stoichiometric ratio of C4H6MnO4·4H2O to NH4VO3 is 0.075:1.925; the black fungus particles are obtained by crushing dry black fungus into small particles of about 1 mm-2 mm with a blunt instrument; the amount of black fungus particles in this embodiment is 0.144 g) Add the reactants into deionized water in sequence under uniform magnetic stirring to fully dissolve and mix for 10 min to obtain a mixed solution, at which time the mixed solution is red;

[0049] (2) Place the fully dissolved mixed solution in a constant temperature oil bath at 80°C and heat and stir until the solution turns blue. Continue heating and stirring until the solution turns into a dark green gel state to obtain a gel state mixture.

[0050] (3) The gel-like mixture is naturally cooled to room temperature, and then transferred to a freeze dryer (-60 °C) and dried overnight to obtain a freeze-dried gel;

[0051] (4) Subsequently, the freeze-dried gel was taken out and ground in a mortar for 30 min, and then transferred to a tube furnace at 300 °C and calcined for 4 h (the first calcination; the first calcination was carried out under an argon atmosphere) to obtain the first calcined product, at which time the material was brown;

[0052] (5) The calcined powder (the first calcined product) was taken out and put into the mortar again for grinding for 30 min. Finally, it was calcined (the second calcination) at 750 °C (5 °C / min heating rate) in a pure argon atmosphere for 6 h (the product obtained after calcination was black), taken out and ground for 30 min to obtain the double-ion doped and wood ear-derived carbon composite modified positive electrode material of this embodiment; that is, Na 2.975 K 0.025 V 1.925 Mn 0.075 (PO4)2F3@3%BF (abbreviated as NKVMPF@3%BF).

[0053] The positive electrode of this embodiment: 70 wt.% NKVMPF@3%BF, 20 wt.% acetylene black and 10 wt.% polyvinylidene fluoride (PVDF) binder (PVDF binder consists of 5 wt.% PVDF solute and 95 wt.% N-methyl-2-pyrrolidone) were weighed and mixed in an agate mortar, stirred and ground into a viscous electrode slurry. The electrode slurry was evenly coated on aluminum foil using a 150nm scraper, vacuum dried at 120 °C for 12 h, and then the dried electrode was cut into circular electrode sheets with a diameter of 11 mm using a slicer.

[0054] The battery of this embodiment: The battery of this embodiment contains the positive electrode as described above. For example, the battery type can be a button half-cell with metallic sodium as the negative electrode.

[0055] Example 2

[0056] The preparation method of the dual-ion doped and wood ear-derived carbon composite modified positive electrode material of this embodiment is different from that of Example 1 only in that the amount of wood ear particles used in step (1) is different. The amount of wood ear particles used in this embodiment is 0.048 g.

[0057] The positive electrode material of this embodiment is Na 2.975 K 0.025 V 1.925 Mn 0.075 (PO4)2F3@1%BF (abbreviated as NKVMPF@1%BF).

[0058] Example 3

[0059] The preparation method of the dual-ion doped and wood ear-derived carbon composite modified positive electrode material of this embodiment is different from that of Example 1 only in that the amount of wood ear particles used in step (1) is different. The amount of wood ear particles used in this embodiment is 0.096 g.

[0060] The positive electrode material of this embodiment is Na 2.975K 0.025 V 1.925 Mn 0.075 (PO4)2F3@2%BF (abbreviated as NKVMPF@2%BF).

[0061] Example 4

[0062] The preparation method of the dual-ion doped and wood ear-derived carbon composite modified positive electrode material of this embodiment is different from that of Example 1 only in that the amount of wood ear particles used in step (1) is different. The amount of wood ear particles used in this embodiment is 0.192 g.

[0063] The positive electrode material of this embodiment is Na 2.975 K 0.025 V 1.925 Mn 0.075 (PO4)2F3@4%BF (abbreviated as NKVMPF@4%BF).

[0064] Example 5

[0065] The preparation method of the dual-ion doped and wood ear-derived carbon composite modified positive electrode material of this embodiment is different from that of Example 1 only in that the amount of wood ear particles used in step (1) is different. The amount of wood ear particles used in this embodiment is 0.240 g.

[0066] The positive electrode material of this embodiment is Na 2.975 K 0.025 V 1.925 Mn 0.075 (PO4)2F3@5%BF (abbreviated as NKVMPF@5%BF).

[0067] Example 6

[0068] The preparation method of the dual-ion doped and wood ear derived carbon composite modified positive electrode material of this embodiment is different from that of embodiment 1 only in that: in step (1), the stoichiometric ratio of KF to NaF is different from that of embodiment 1 (the stoichiometric ratio of KF to NaF is 0.01:2.99 and 0.04:2.96, respectively).

[0069] The positive electrode materials of this embodiment are Na 2.99 K 0.01 V 1.925 Mn 0.075 (PO4)2F3@3%BF (abbreviated as NK 0.01 VMPF@3%BF)、Na 2.96 K 0.04 V 1.925 Mn 0.075(PO4)2F3@3%BF (abbreviated as NK 0.04 VMPF@3%BF).

[0070] Example 7

[0071] The preparation method of the dual-ion doped and wood ear derived carbon composite modified positive electrode material of this embodiment is different from that of Example 1 only in that: in step (1), the stoichiometric ratio of C4H6MnO4·4H2O to NH4VO3 is different from that of Example 1 (the stoichiometric ratio of C4H6MnO4·4H2O to NH4VO3 is 0.05:1.95 and 0.1:1.9, respectively).

[0072] The positive electrode materials of this embodiment are Na 2.975 K 0.025 V 1.95 Mn 0.05 (PO4)2F3@3%BF(abbreviated as NKVM 0.05 PF@3%BF)、Na 2.975 K 0.025 V 1.9 Mn 0.1 (PO4)2F3@3%BF(abbreviated as NKVM 0.1 PF@3%BF).

[0073] Comparative Example 1

[0074] The difference between this comparative example and Example 1 is that KF, C4H6MnO4·4H2O and fungus particles in step (1) are omitted; the rest are consistent with Example 1.

[0075] The product prepared in this comparative example is Na3V2(PO4)2F3 (abbreviated as NVPF) positive electrode material.

[0076] Comparative Example 2

[0077] The difference between this comparative example and Example 1 is that the C4H6MnO4·4H2O and the fungus particles in step (1) are omitted, and the stoichiometric ratios of KF to NaF are 0.01:2.99, 0.025:2.975 and 0.04:2.96 respectively; the rest are consistent with Example 1.

[0078] The products prepared in this comparative example are Na 2.99 K 0.01 V2(PO4)2F3 (abbreviated as NK 0.01 VPF)、Na 2.975 K 0.025 V2(PO4)2F3 (abbreviated as NK 0.025 VPF) and Na2.96 K 0.04 V2(PO4)2F3 (abbreviated as NK 0.04 VPF).

[0079] Comparative Example 3

[0080] The difference between this comparative example and Example 1 is that KF and wood ear particles in step (1) are omitted, and the stoichiometric ratios of C4H6MnO4·4H2O and NH4VO3 are 0.05:1.95, 0.075:1.925 and 0.1:1.9 respectively; the rest are consistent with Example 1.

[0081] The products prepared in this comparative example are Na3V 1.95 Mn 0.05 (PO4)2F3 (abbreviated as NVM 0.05 PF), Na3V 1.925 Mn 0.075 (PO4)2F3 (abbreviated as NVM 0.075 PF) and Na3V 1.9 Mn 0.1 (PO4)2F3 (abbreviated as NVM 0.1 PF).

[0082] Comparative Example 4

[0083] The difference between this comparative example and Example 1 is that the fungus particles in step (1) are omitted; the rest are consistent with Example 1.

[0084] The product prepared in this comparative example is Na 2.975 K 0.025 V 1.925 Mn 0.075 (PO4)2F3 (abbreviated as NKVMPF).

[0085] Comparative Example 5

[0086] The only difference between this comparative example and Example 1 is that the fungus particles are replaced with an equal amount of pomelo peel (fresh white pomelo peel is taken, the yellow outer skin is removed and cut into small square pieces of 1 cm×1 cm×1 cm with a utility knife. The cut pomelo peel is washed with deionized water for 5 times and then placed in a vacuum freeze dryer to dry overnight); the rest is consistent with Example 1.

[0087] The product prepared in this comparative example is Na 2.975 K 0.025 V 1.925 Mn 0.075 (PO4)2F3@PP (abbreviated as NKVMPF@PP).

[0088] Comparative Example 6

[0089] The difference between this comparative example and Example 1 is that the fungus particles are replaced with an equal amount of ramie (fresh ramie stem bark is taken and cut into small pieces of 1 mm. The cut ramie is washed with deionized water for 4 times and then placed in a vacuum freeze dryer to dry overnight); the rest is consistent with Example 1.

[0090] The product prepared in this comparative example is Na 2.975 K 0.025 V 1.925 Mn 0.075 (PO4)2F3@RF (abbreviated as NKVMPF@RF).

[0091] Experimental example:

[0092] 1. Phase characterization

[0093] (1) X-ray diffraction

[0094] X-ray diffractometer (XRD) is a common instrument for material phase and crystal structure analysis. The D8AD VANCE X-ray diffractometer produced by Bruker, Germany was used. Cu-Kα was used as the radiation source (λ=0.15418 nm), the tube voltage was 40 kV, the tube current was 40 A, the scanning angle was 10-90°, and the scanning speed was 0.2 s / step.

[0095] The XRD patterns of the positive electrode materials of NKVMPF@1%BF (Example 2), NKVMPF@2%BF (Example 3), NKVMPF@3%BF (Example 1), NKVMPF@4%BF (Example 4), NKVMPF@5%BF (Example 5) and NKVMPF (Comparative Example 4) are shown in FIG. Figure 1 shown.

[0096] Depend on Figure 1 It can be seen that the main diffraction peaks of the six groups of materials correspond to the standard card (PDF#89-8485) of Na3V2(PO4)2F3, and all samples have the same structural characteristics (tetragonal NASICON lattice, space group P42 / mnm) and high crystallinity. Only a small amount of low-intensity diffraction peaks belong to Na3V2(PO4)3, and the corresponding standard card is PDF#53-0018. This shows that the material will not change its original tetragonal crystal structure after being compounded with wood ear-derived carbon. It can be seen from the figure that there is no characteristic peak of carbon in the material, indicating that the wood ear exists in the material in the form of amorphous carbon after high-temperature decomposition. Figure 1 (b) is a locally enlarged XRD pattern. Compared with the NKVMPF positive electrode material, the peak of the (220) lattice plane of the NKVMPF@3%BF positive electrode material has not shifted.

[0097] (2) Scanning electron microscopy

[0098] Scanning electron microscopy (SEM) is an important means to observe the morphology and microstructure of surface samples. A SU8010 scanning electron microscope produced by Hitachi of Japan was used, and a HITACHI MC1000 gold spraying instrument was used for gold spraying. The gold spraying time was 120 s, and the electron microscope test voltage was 5 kV.

[0099] The morphologies of NKVMPF (Comparative Example 4), NKVMPF@1%BF (Example 2), NKVMPF@2%BF (Example 3), NKVMPF@3%BF (Example 1), NKVMPF@4%BF (Example 4) and NKVMPF@5%BF (Example 5) were characterized by scanning electron microscopy (SEM) and typical energy dispersive X-ray (EDS) spectra (the corresponding SEM images are shown in the figure below). Figure 2 (a)-(f)). The material particles of the composite wood ear derived carbon grow inside and outside the pores of the derived carbon, and the surface of the material particles becomes smoother. The SEM images of the NKVMPF@3%BF composite are shown in Figure 2 (d) as shown.

[0100] In addition, the EDS element mapping of the NKVMPF@3%BF composite material was further observed, and the element quantification data are shown in Table 1. The Na, K, V, Mn, P, O, and F elements are evenly distributed in the particles of the NKVMPF@3%BF material, and the data in Table 1 show that the contents of K and Mn elements are 0.74% and 1.06%, respectively, which basically corresponds to the theoretical contents of K and Mn elements (0.14% and 0.53%), further confirming that K + and Mn 2+ It was successfully incorporated into NVPF material particles.

[0101] Table 1

[0102]

[0103] (3) Transmission electron microscopy

[0104] Transmission electron microscopy (TEM) has a higher resolution and is an important means to further analyze the microstructure and lattice fringes of materials. The Talos F200i transmission electron microscope produced by Thermo Fisher Scientific was used, and the test voltage was 200 kV.

[0105] Transmission electron microscopy images Figure 3 Shown ((a) is the TEM image of NKVMPF@3%BF; (b) is the HRTEM image of NKVMPF@3%BF).

[0106] from Figure 3 The lattice fringes of the NKVMPF@3%BF cathode material can be clearly found in (b), which indicates that the NKVMPF@3%BF cathode material has a high degree of crystallinity and a complete crystal structure; the NKVMPF@3%BF cathode material is composed of small unit material particles, and the material particles are coated with a relatively thin carbon layer, which can improve the electronic conductivity of the material. The lattice spacing is 0.64 nm, corresponding to the (110) crystal plane of the NVPF material. This is consistent with the XRD test results.

[0107] Using the same method to observe NKVMPF (Comparative Example 4) and NVPF (Comparative Example 1) using a transmission electron microscope, it can be found that the lattice spacing of NKVMPF is 0.64 nm, and the lattice spacing of NVPF is 0.63 nm. + and Mn 2+ The doping of can expand the lattice spacing of NVPF, which is Na + Provides a larger transmission channel, which is beneficial to Na + It can also help to alleviate the volume expansion of the material during the electrochemical process, thereby improving the performance of sodium-ion batteries.

[0108] (4) Thermogravimetry

[0109] Thermogravimetric analysis (TG) is a common method for analyzing the relationship between sample mass and temperature change under programmed temperature control conditions. It mainly analyzes the internal water content and thermal stability of the material. The TGA / DSC3+ thermal analyzer from Mettler-Toledo, Switzerland, was used, an alumina crucible was used, the test conditions were air atmosphere, the temperature rise range was 50-600 °C, and the heating rate was 10 °C / min.

[0110] The test results are as follows Figure 4 shown.

[0111] Depend on Figure 4 It can be seen that the weight loss rates of NKVMPF (Comparative Example 4) and NKVMPF@3%BF (Example 1) at 500 °C are 7.347% and 11.542%, respectively. The difference in carbon content between the two groups of materials is 4.195%, which comes from the wood ear-derived carbon and is basically consistent with the theoretical carbon content added. The weight loss of the material can be attributed to the removal of adsorbed water and the decomposition of the remaining organic ligands. The weight loss in the range of 50-200 °C corresponds to the removal of adsorbed water, and the weight loss after 200 °C is attributed to the oxidative decomposition of the organism.

[0112] (5) XPS analysis:

[0113] The element valence state of NKVMPF@3%BF composite material was studied by XPS spectrum analysis. The test results are as follows: Figure 5-7 shown. Figure 5 The full spectrum proves the presence of Na, K, V, Mn, P, O, F and C elements in the material. Figure 6 (a) shows K 2p XPS spectrum, the C potential was adjusted to the standard potential of 284.8 eV by using the software Avantage. 2p The two peaks in the graph are 296.0 eV and 293.1 eV, respectively, which proves that K + was successfully introduced into the crystal structure. Figure 6 (b) shows the Mn 2p XPS spectrum of Mn 2p The four peaks in the graph are 654.3 eV, 652.8 eV, 644.5 eV, and 641.4 eV, respectively. This proves that Mn 2+ was successfully introduced into the crystal structure. Figure 6 (c) shows C 1s XPS spectrum, C 1s The three peaks in the graph are at 288.2 eV, 286.2 eV, and 284.8 eV, which are attributed to the carbon in C=C, CC, and CO, respectively. Figure 6 (d) shows V 2p XPS spectrum shows two spin-orbit doublets (V 2p 3 / 2 and V 2p 1 / 2 ), the binding energies are 524.2 eV and 517.1 eV, which are V 3+ characteristic peaks. Figure 7 (a) shows O 1s The XPS spectrum shows three peaks with binding energies of 536.0 eV, 533.3 eV, and 531.3 eV. The strongest peak at 536.0 eV is a typical characteristic peak of metal-oxygen bonds, which can be attributed to lattice oxygen in the spinel structure, the peak at 533.3 eV is related to the -OH group, and the peak at 531.3 eV corresponds to water physically or chemically adsorbed on the surface. Figure 7 As shown in (b)-(d), the peaks at 133.4 eV, 684.7 eV, and 1071.8 eV are respectively attributed to P 2p 、F 1s and Na 1s The binding energy.

[0114] (6) Specific surface area

[0115] Specific surface area analysis (BET) is a method of obtaining the specific surface area of ​​a material by calculating the amount of gas adsorbed on the surface of a material by a single molecular layer. The 3020 specific surface area analyzer produced by the American company Micromeritics was used, the adsorbed gas was nitrogen, and the test temperature was 77 K.

[0116] Figure 8 (a) and (b) are the adsorption / desorption curves of NKVMPF (Comparative Example 4) and NKVMPF@3%BF positive electrode materials (Example 1), respectively. Both NKVMPF and NKVMPF@3%BF positive electrode materials show typical IV type adsorption isotherms, and there is an obvious H3 type hysteresis loop at 0.4-1.0P / P0, which shows that the prepared NKVMPF and NKVMPF@3%BF positive electrode materials have typical mesoporous properties. Moreover, it can be seen from the pore size distribution diagram of the material that most of the pore size of the material is concentrated within 10 nm. The specific surface areas of the two materials calculated by BET are 61.08 m 2 / g and 94.76 m 2 / g. By comparing the data, it is found that the specific surface area of ​​the NKVMPF@3%BF composite material with wood ear derived carbon is 33.68 m larger than that of the NKVMPF material without wood ear derived carbon. 2 / g. High specific surface area can not only promote the infiltration of electrolyte, but also provide more active sites for the material, accelerate the diffusion of sodium ions, and improve the discharge capacity of the material.

[0117] 2. Electrochemical performance test

[0118] I. Test preparation:

[0119] (1) Preparation of electrode sheets:

[0120] Preparation of positive electrode sheet: 70 wt.% of active material (positive electrode material prepared in the above examples and comparative examples), 20 wt.% of acetylene black and 10 wt.% of polyvinylidene fluoride (PVDF) binder were weighed and mixed in an agate mortar, stirred and ground into a viscous electrode slurry. The PVDF binder consists of 5 wt.% PVDF solute and 95 wt.% N-methyl-2-pyrrolidone (NMP). The electrode slurry was evenly coated on aluminum foil using a 150 nm scraper, vacuum dried at 120 ° C for 12 h, and then the dried electrode sheet was cut into a circular electrode sheet with a diameter of 11 mm using a slicer.

[0121] Preparation of negative electrode sheet: In a glove box, shave off the oxide layer on the metal surface, flatten it, and cut it into circular sheets with a thickness of about 1 mm.

[0122] (2) Battery assembly:

[0123] The battery types in the experiment are all button half-cells with metallic sodium as the negative electrode. The assembly operation is carried out in a glove box filled with argon gas. The assembly order is: negative electrode shell, sodium sheet, diaphragm, electrolyte, positive electrode sheet, gasket, spring, positive electrode shell. After the battery is assembled, it is sealed with a hydraulic press, and the battery is left to stand for 12 hours to allow the electrolyte to fully infiltrate the diaphragm and the electrode.

[0124] The main materials required for battery assembly: glass fiber separator (specification: No.1823-047), manufactured by Whatman; electrolyte (specification: 1.0 M NaClO4 (EC:PC=1:1 Vol%)), manufactured by Duoduo Reagent; battery shell (specification: CR2032), manufactured by CROOD; sodium sheet (specification: D=11 mm), manufactured by CROOD; button battery packaging machine (MSK-110), manufactured by Shenzhen Kejing Zhida Technology Co., Ltd.

[0125] II. Test methods:

[0126] (1) Charge and discharge test: Charge and discharge test is an important means to test the electrochemical properties of materials. All batteries are tested using a new VELCRO battery tester (model: CT-4008) with a voltage range of 2-4 V and a constant temperature chamber set at 25 °C.

[0127] (2) Cyclic voltammetry test: Cyclic voltammetry (CV) can be used to observe the redox potential, electrochemical reaction activity and reaction mechanism of the electrode. The assembled button cell was tested using a CHI660E electrochemical workstation from Shanghai Chenhua Instrument Factory.

[0128] (3) Electrochemical impedance spectroscopy (EIS) is a method of measuring the change in impedance phase angle and sine wave frequency by applying a small amplitude AC voltage. The assembled battery was subjected to an electrochemical impedance spectroscopy test using a Shanghai Chenhua CHI660E electrochemical workstation. At room temperature, the FT scanning mode was used, and the open circuit voltage of the battery was set as the starting voltage. The voltage was varied between 0.01 Hz and 10 5 The battery samples were tested in the frequency range of Hz.

[0129] III. Test results:

[0130] (1) Cyclic performance and rate performance at 0.2 C:

[0131] The cycle performance of the positive electrode materials of NKVMPF@3%BF (Example 1), NKVMPF@1%BF (Example 2), NKVMPF@2%BF (Example 3), NKVMPF@4%BF (Example 4), NKVMPF@5%BF (Example 5) and NKVMPF (Comparative Example 4) at 0.2 C is shown in the figure. Fig. 9 (a) shows the rate performance diagram of 10 cycles at current densities of 0.2 C, 0.5 C, 1 C, 2 C, and 5 C. Fig. 9 (b) as shown.

[0132] The discharge capacity of the positive electrode materials of Examples 1-5 first increases and then decreases with the increase of the amount of derived carbon added. Among them, the first cycle discharge capacity of the NKVMPF@3%BF (Example 1) composite material is 115.36 mAh / g, and the capacity is 118.66 mAh / g after 200 cycles, the capacity retention rate is as high as 102.86%, and the coulomb efficiency after 200 cycles is 95.54%. The first cycle discharge capacity of the positive electrode material of Comparative Example 4 without composite fungus derived carbon material is 116.49 mAh / g, and the capacity is 109.79 mAh / g after 200 cycles, and the capacity retention rate is 94.24% (see Table 2 below for details).

[0133] The rate performance of the positive electrode materials of Examples 1-5 first increases and then decreases with the increase of the amount of derived carbon added. Among them, the discharge specific capacity of the NKVMPF@3%BF positive electrode material at each rate is higher than that of NKVMPF. Moreover, when the NKVMPF@3%BF composite material returns to the rate of 0.2 C through the rate test, it can still maintain a reversible specific capacity of 119.17 mAh / g, and has a discharge specific capacity of 108.76 mAh / g at a high rate of 5 C. The reversible specific capacity of the NKVMPF material returning to the rate of 0.2 C is 112.43 mAh / g, and the discharge specific capacity at a high rate of 5 C is 105.71 mAh / g.

[0134] Similarly, the charge and discharge data of the positive electrode materials of Comparative Examples 1-3 and Comparative Examples 5-6 at 0.2 C were tested using the same method, and the test results are shown in Table 2 below:

[0135] Table 2

[0136]

[0137] The same method was used to test the rate performance of the positive electrode materials of Comparative Example 2 and Comparative Example 3. The test results were: NK 0.025 The VPF has a reversible capacity of 110.47 mAh / g at a rate of 0.2 C through rate testing, and a discharge capacity of 99.76 mAh / g at a high rate of 5 C. 0.075 The reversible specific capacity of PF at a rate of 0.2 C was 110.12 mAh / g through rate testing, and the discharge specific capacity at a high rate of 5 C was 105.53 mAh / g.

[0138] (2) Cyclic voltammetry test:

[0139] Cyclic voltammetry was performed at 2.5-4.3 V at a scan rate of 0.1 mV / s. The CV curves obtained are shown in Fig.10 shown. Fig.10 The samples corresponding to (a)-(f) are: (a) NKVMPF (Comparative Example 4), (b) NKVMPF@1%BF (Example 2), (c) NKVMPF@2%BF (Example 3), (d) NKVMPF@3%BF (Example 1), (e) NKVMPF@4%BF (Example 4), and (f) NKVMPF@5%BF (Example 5).

[0140] Three pairs of redox peaks were observed for all samples at 3.50 / 3.27, 3.76 / 3.65, and 4.22 / 4.14 V, respectively, indicating that the addition of wood ear-derived carbon does not change the electrochemical behavior of NKVMPF materials. Among them, the coincidence of the CV curves of the NKVMPF3%@BF cathode material in the first three weeks is significantly better than that of the other five groups of materials, indicating that the NKVMPF3%@BF composite material has better cycle stability and reversibility, which is also consistent with the results of the cycle performance diagram.

[0141] (3) Electrochemical impedance spectroscopy and first-week charge-discharge curve test:

[0142] The electrochemical impedance spectroscopy of NKVMPF (Comparative Example 4), NKVMPF@1%BF (Example 2), NKVMPF@2%BF (Example 3), NKVMPF@3%BF (Example 1), NKVMPF@4%BF (Example 4) and NKVMPF@5%BF (Example 5) are shown in FIG. Fig.11 (a) The R1 value of NKVMPF@3%BF is significantly lower than that of the composite materials with other ratios (see Table 3 for specific values). This is attributed to the three-dimensional conductive porous structure of wood ear derived carbon, which enhances the conductivity of the material and promotes the electron and Na + Transport inside the electrode.

[0143] The first week charge and discharge curves of NKVMPF (Comparative Example 4), (b) NKVMPF @ 1% BF (Example 2), (c) NKVMPF @ 2% BF (Example 3), (d) NKVMPF @ 3% BF (Example 1), (e) NKVMPF @ 4% BF (Example 4) and (f) NKVMPF @ 5% BF (Example 5) are as follows: Fig.11As shown in (b), the charge-discharge curves of the five groups of positive electrode materials in Examples 1-5 are similar, and there are three pairs of charge-discharge platforms in the first week charge-discharge curves of the five groups of positive electrode materials in Examples 1-5 and the NKVMPF positive electrode material, which are consistent with the positions of the three pairs of redox peaks in the CV curve diagram of the material.

[0144] (4) Z' (real part of impedance) and ω in the low frequency range -1 / 2 The relationship curve between:

[0145] Fig.12 The Z' and ω of NKVMPF (Comparative Example 4), NKVMPF@1%BF (Example 2), NKVMPF@2%BF (Example 3), NKVMPF@3%BF (Example 1), NKVMPF@4%BF (Example 4) and NKVMPF@5%BF (Example 5) electrodes in the low-frequency Warburg region are shown. -1 / 2 By comparison, it can be found that the Warburg diffusion impedance of the positive electrode material of NKVMPF@3%BF (Example 1) is the smallest because the porous carbon conductive structure derived from fungus is + The extraction / embedding of ions and the transmission of electrons play a good role in promoting the reduction of electrode impedance and the improvement of the reaction kinetics of materials. -1 / 2 The slope σ was obtained by fitting the straight line (Equation (1)). The diffusion coefficient of sodium ions of a series of composite electrodes was calculated using the following equation (2).

[0146] (1)

[0147] (2)

[0148] Among them, R s is the ohmic resistance, R1 is the charge transfer impedance, and D is Na + diffusion coefficient, R is the gas constant (8.314 J / K / mol), T is the test temperature, A represents the surface area of ​​the electrode, n represents the number of electrons transferred per mole of redox reaction, F is the Faraday constant (96486 C / mol), C is Na + Ion concentration, σ represents the Warburg impedance factor. After calculation, the value of the Warburg impedance factor σ of each electrode and the diffusion coefficient of sodium ions are obtained. The kinetic parameters of each electrode are shown in Table 3 below. The smaller the σ value, the corresponding sodium ion diffusion coefficient D Na +The larger the value, the greater the value. From the calculation results, it can be seen that the wood ear derived carbon composite can reduce the Warburg impedance of the material, increase the diffusion coefficient of sodium ions, and enhance the charge and discharge performance of the material under large current. Among them, the σ value of the NKVMPF@3%BF composite material is the smallest, and the corresponding calculated sodium ion diffusion coefficient is 1.65×10 -13 cm 2 / s.

[0149] Table 3

[0150]

[0151] (5) Charge and discharge curves of each week:

[0152] Fig.13 Among them, (a) is NKVMPF (Comparative Example 4), (b) is NKVMPF@1%BF (Example 2), (c) is NKVMPF@2%BF (Example 3), (d) is NKVMPF@3%BF (Example 1), (e) is NKVMPF@4%BF (Example 4), and (f) is NKVMPF@5%BF (Example 5) The weekly charge and discharge curves of the positive electrode materials. In the subsequent cycle process, the discharge curve of NKVMPF@3%BF is the most intensive and the voltage platform change is also the smallest. It can also be concluded from the previous cycle performance diagram that the capacity retention rate of NKVMPF@3%BF is higher, that is, the attenuation degree of its discharge specific capacity is smaller, which is consistent with its intensive charge and discharge curve.

[0153] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a positive electrode material of dual ion doping and wood ear derived carbon composite modification, characterized in that: The steps include: (1) NaF, KF, NH4H2PO4, NH4VO3, C4H6MnO4·4H2O, citric acid monohydrate and fungus particles are sequentially added into water under stirring and dispersed uniformly to obtain a mixed solution; (2) heating and stirring the mixed solution to obtain a gel-like mixture; (3) cooling and freeze-drying to obtain freeze-dried gel; (4) grinding the freeze-dried gel, and performing a first calcination after grinding to obtain a first calcined product; (5) grinding the first calcined product, and then calcining it for a second time after grinding, so as to obtain the positive electrode material of the double ion doping and wood ear derived carbon composite modification; the positive electrode material of the double ion doping and wood ear derived carbon composite modification is Na 3- x K x V 2-y Mn y (PO4)2F3@BF; In step (4), the temperature of the first calcination is 250-350°C and the calcination time is 3.5-4.5 h; In step (5), the second calcination is carried out in an argon environment, the temperature of the second calcination is 710-790°C, and the calcination time is 5.0-6.5 h; Na 3-x K x V 2-y Mn y (PO4)2F3@BF, where x = 0.01 - 0.04 and y = 0.05 - 0.1; Na 3-x K x V 2-y Mn y In (PO4)2F3@BF, the mass percentage of wood ear-derived carbon is 3%.

2. The method for preparing the dual ion doped and wood ear derived carbon composite modified positive electrode material according to claim 1, characterized in that: In step (2), the heating temperature is 60-100°C; In step (3), the freeze-drying temperature is -70~-50°C.

3. The method for preparing the dual-ion doped and wood ear derived carbon composite modified positive electrode material according to claim 1, characterized in that: The particle size of the fungus particles is 1-2 mm.

4. A positive electrode material of dual ion doping and wood ear derived carbon composite modification, characterized in that: The dual-ion doped and wood ear-derived carbon composite modified positive electrode material is prepared by the method according to any one of claims 1 to 3.

5. A positive electrode, characterized in that The positive electrode adopts the double-ion doped and wood ear derived carbon composite modified positive electrode material as claimed in claim 4.

6. A sodium ion battery, characterized in that: The sodium ion battery adopts the positive electrode as claimed in claim 5.